2020
DOI: 10.4028/www.scientific.net/kem.844.124
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Sinter Production with Wood Biomass Application

Abstract: A large amount of finely dispersed manganese ore left after benefication operations or blown out from the furnaces is unsuitable for direct use in electric furnaces and blast furnaces, therefore it is necessary to granulate it in order to have the efficient use of its fine ore particles in metallurgy. To make our research more of practical use, we found it is reasonable not only work over manganese fines sintering but also to attempt mitigating the negative effect on the environment produced by the further sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The performance of HSCs based on the synthesized materials was investigated in a two-electrode cell. As a negative (polarized) electrode used nanoporous carbon [18,19], the positive electrode was the synthesized material in each case. The electrolyte was a 3.5 M aqueous solution of KOH.…”
Section: Methodsmentioning
confidence: 99%
“…The performance of HSCs based on the synthesized materials was investigated in a two-electrode cell. As a negative (polarized) electrode used nanoporous carbon [18,19], the positive electrode was the synthesized material in each case. The electrolyte was a 3.5 M aqueous solution of KOH.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, agglomeration of those fines is necessary. One possible way is to sinter the fines [43]. The main function of sintering machines is to agglomerate fines, in addition, it is possible to reduce the oxides, even if this secondary effect is limited [155].…”
Section: Solid-state Processes Using Bio-based Carbon For the Production Of Manganese Alloysmentioning
confidence: 99%
“…al. [43] carried out a laboratory study using coke breeze and mixtures of coke breeze with 25% woody biomass or prepyrolyzed wood as fuel for sintering manganese ore, manganese concentrate, fluxes and returns. It was observed that the yield of sinter with a size over 10 mm and the specific sintering capacity decreased by substituting coke breeze with biomass.…”
Section: Solid-state Processes Using Bio-based Carbon For the Production Of Manganese Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Metallurgy is increasingly shifting its focus to more sustainable and environmentally conscious production practices, faced with a changing climate and the societal impact of harmful pollutants. The prospects of using biomass in metallurgy as a fuel and reducing agents for iron ore sintering and reduction of iron [14,15] have been considered promising [8][9][10][11][12][13]. Biogas application instead of natural gas also has environmental and economic benefits [16,17].…”
Section: Introductionmentioning
confidence: 99%